Genetic diversity of two Southern African cichlids (Oreochromis andersonii and O. macrochir) in the Zambezi and Congo River basins. (20th December 2019) - Bbole, Ian; Zhao, Jin‐Liang; Tang, Shou‐Jie; Katongo, Cyprian
Abstract: Oreochromis andersonii and O. macrochir are two important cichlid species native to Southern Africa. We describe in this paper their genetic population structure in the Upper Zambezi River, Kafue River, and Lake Bangweulu representing part of the Congo and Zambezi River Basins. Microsatellite genetic markers were employed to analyse the genetic population structure of the two species using 177 tissue samples. The average allele richness of O. andersonii was higher in the Zambezi River (10.500) than in the Kafue River (9.583) though not statistically different. For O. macrochir, it was highest in the Zambezi River (11.170) followed by the Kafue River (9.781) and least in Lake Bangweulu (7.067) and their differences were significant. The gene diversity indices; gene diversity ( h s), observed heterozygosity ( H O ), expected heterozygosity ( H E ) were high and similar in O. andersonii populations. However, in O. macrochir H E was significantly lower in Lake Bangweulu (0.678) compared to the Kafue River (0.799) and Zambezi River (0.802) populations. Population differentiation estimated by R ST and D EST revealed high differentiation in both species ( R ST  = 0.598, D EST  = 0.777 for O. andersonii ; R ST  = 0.379, D EST  = 0.710 for O. macrochir ). The highest source of variation was among populations (84.71%) for O. andersonii and within populations (67.09%) for O. macrochir . Comparisons of population pairs revealed a close genetic similarity between the Zambezi River and Lake Bangweulu populations of O. macrochir . Bottlenecks were observed in both species using the Two‐Phase Model (T.P.M.) indicative of a recent genetic loss or reduction in effective population size. Though our results indicate that the populations of both species still maintain sufficiently high levels of genetic diversity in the sampled areas, the bottlenecks observed are a source of concern. We recommend a more robust study of genetic diversity of these species in all sections of these river systems and that some key conservation sites should be identified to protect the gene pool of these native species.